A PRELIMINARY STUDY ON NEW UNDERGRADUATES’ EXPERIENCE OF UNDERTAKING ONLINE ASSESSMENTS FOR ENGLISH POST COVID-19 PANDEMIC - Ahmad, Badrul Hisham; Ismail, Syafini; Ab Rahim, Ina Suryani; Ahmad, Norkhairi bin (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
This initial study set out to investigate university freshmen’s feedback on their online assessment experience using the university’s learning management system in their English Language course which was conducted online. The objectives of this study were to investigate a) the learners’ perception on their overall online assessment experience for a language course using the university’s LMS, b) the learners’ experience in completing a writing assessment and c) the learners’ experience in completing a listening assessment. This basic mix-method study investigated 27 English Language learners of a public university in Malaysia attending Level 1 English proficiency course. A questionnaire containing 17 items using 5-points Likert-type scale was administered to measure their general online experience and their writing and listening assessment experience using the university LMS. This was followed by a round semi-structured interviews to probe further reasons behind their perception and experience. The study found that the freshmen expressed positive perception towards their overall online language assessment experience. They also indicated positive feedback for their experience in taking online writing and listening assessments Through the interviews the students highlighted that they are able to familiarize themselves and adapt faster by drawing on their previous experience during online learning at home during Covid-19 pandemic for their high school studies. They learnt to be patient and not panicky whenever there is any technical glitch which they had faced quite a lot during the pandemic. This shows that the students have developed certain level of literacy and digital education competency.